Successful minimally invasive two‐stage operation for rare synchronous cancers of the esophagus and the pancreatic head: A case report. Issue 3 (9th December 2019) - Ozawa, Hiroki; Kawakubo, Hirofumi; Kitago, Minoru; Mayanagi, Shuhei; Fukuda, Kazumasa; Nakamura, Rieko; Suda, Koichi; Wada, Norihito; Kitagawa, Yuko
Abstract: We report the case of a 70‐year‐old woman with synchronous advanced esophageal cancer and pancreatic head cancer. To reduce the surgical invasiveness, we performed a two‐stage operation that included percutaneous endoscopic gastrostomy and minimally invasive esophagectomy. In the first stage, we performed a percutaneous endoscopic gastrostomy, a thoracoscopic esophagectomy with cervical and mediastinal lymph node dissection, and an esophagostomy without a laparotomy. The second stage, which was performed 28 days after the first operation, consisted of a total gastrectomy, pancreaticoduodenectomy, colonic reconstruction, and jejunostomy. Fifty days after the second operation, the patient was discharged from the hospital. A two‐stage operation that includes minimally invasive esophagectomy seems to be useful for avoiding serious postoperative complications, even in patients with rare, synchronous advanced cancers of the esophagus and the pancreatic head.